Financial Performance Analysis of KSP KOPDIT Pintu Air based on PEARLS Method - Gabriel Pito; Titik Mildawati; Fidiana (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aimed to determine the analysis result of financial performance using PEARL (Protection, Effective Financial Structure, Asset Quality, Rates of Return and Costs, Liquidity, and Signs of Growth) at KSP Kopdit Pintu Air from 2017-up to 2021. The study used descriptive-quantitative research. Furthermore, the variable was the financial performance of KSP Kopdit Pintu Air. Based on the PEARL method, the study used 13 ratios and two kinds of data sources, namely, primary and secondary. As a result, it showed that the financial performance of KSP Kopdit Pintu Air which used 13 ratios from the PEARLS method was, still lacks performance or in an unhealthy situation. It happened as within the 13 ratios; many ratios were on average.